2022
DOI: 10.1155/2022/6756676
|View full text |Cite|
|
Sign up to set email alerts
|

Timosaponin AIII Suppresses RAP1 Signaling Pathway to Enhance the Inhibitory Effect of Paclitaxel on Nasopharyngeal Carcinoma

Abstract: Although PTX has been identified as an effective drug for nasopharyngeal carcinoma (NPC) therapy, it has serious side effects in the human body. Previous studies have shown that timosaponin AIII (TSAIII) can inhibit the malignant progression of NPC cells. This study investigated the active mechanism of the combination of TSAIII and paclitaxel (PTX) on NPC. Cellular viability, apoptosis, apoptotic factors, and RAP1 signaling regulators were detected in the PNC cells (CNE-1 and HNE-2) and the subcutaneous CNE-1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
(36 reference statements)
0
4
0
Order By: Relevance
“…Active ingredients isolated from traditional medical herbs are considered promising and potentially valuable resources for developing anticancer drugs. TIA has recently received particular attention for its potential to be developed as an anticancer agent [29] because TIA has been demonstrated to exert potent and diverse antitumor activities including interfering with invasion and migration [30][31][32][33][34], autophagy [35][36][37], reversing drug resistance [38][39][40][41], and inducing apoptosis [42][43][44][45][46][47]. However, the effect of TIA on glioblastoma tumorigeneity remains unanswered.…”
Section: Discussionmentioning
confidence: 99%
“…Active ingredients isolated from traditional medical herbs are considered promising and potentially valuable resources for developing anticancer drugs. TIA has recently received particular attention for its potential to be developed as an anticancer agent [29] because TIA has been demonstrated to exert potent and diverse antitumor activities including interfering with invasion and migration [30][31][32][33][34], autophagy [35][36][37], reversing drug resistance [38][39][40][41], and inducing apoptosis [42][43][44][45][46][47]. However, the effect of TIA on glioblastoma tumorigeneity remains unanswered.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that TSAIII strengthens the suppressive activity of paclitaxel (PTX) on the proliferation of nasopharyngeal carcinoma CNE-1 and HNE-2 cells, upregulates the expression of Bad and RAP1GAP, downregulates the expression of Bcl-2, RAP1, and RasGRP2, and promotes PTX-induced apoptosis. TSAIII can synergize with PTX to protect against tumor growth in a xenograft mouse model [ 45 ] ( Table 1 ).…”
Section: The Anticancer Effects Of Tsaiiimentioning
confidence: 99%
“…The microwells had flat bottoms instead of curved ones, enabling the evaluation of cell migratory behavior. PTX has been identified as a candidate for the treatment of nasopharyngeal carcinoma (NPC), but additional measures are needed to suppress its side effects and enhance its delivery efficiency [ 27 , 28 ]. For the first time, PEGylated paclitaxel nanoparticles (PEG-PTX NPs) were applied to treat NPC43 cells in microwells without and with a cover.…”
Section: Introductionmentioning
confidence: 99%